Resilience as a Key to Becoming a Strong and Adaptive Individual - Dwi Prasetyo Rini (DEVOTIONIS, 2026)
Resilience refers to an individual's capacity to recover from adversity, manage stress, and regain physical, psychological, and social stability after experiencing difficult life events. This article aims to examine the extent to which individuals develop resilience and to identify the personal and environmental factors that support or hinder resilient functioning. The study used a literature review approach by analyzing selected national and international journal articles, books, and relevant academic sources on resilience, self-esteem, social support, school well-being, toxic relationships, parental divorce, and self-harm history. The reviewed literature indicates that resilience is shaped by the interaction between risk factors, such as trauma, anxiety, pressure, and negative life experiences, and protective factors, such as self-esteem, peer support, emotional regulation, school well-being, and positive meaning-making. Several studies show that individuals exposed to stressful or adverse conditions often demonstrate low to moderate resilience, particularly when they lack effective coping strategies and supportive social systems. Therefore, resilience should not be understood merely as the ability to endure hardship, but as a dynamic developmental process that enables individuals to recover, adapt, learn from adversity, and construct a more meaningful future. The findings imply that guidance and counseling services should strengthen resilience through preventive, developmental, and restorative interventions that promote self-understanding, emotional regulation, optimism, and adaptive coping.